Mineral and Insilico Study of Sapat Siam Fish (Trichopodus pectoralis, Regan 1910) on Appetite Regulation - Rosadi, Erwin; Budiarti, Lia Yulia; Putra, Andifa Anugerah; Rahmah, Resvi Amalia; Qiptiah, Putri Mariatul; Isnaini, Isnaini (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Backgrounds: Production of Sapat siam fish is ranked second after Papuyu. Giving fish in cases of wasting can overcome mineral deficiencies in wasting sufferers, because fish contains minerals. Wasting sufferers experience Fe, Ca and Zn deficiencies. There is a relationship between cases of wasting and the incidence of anemia. Anemia sufferers experience a decrease in appetite. Until now, there is no known effect of giving the minerals Fe, Ca and Zn on appetite regulation. Objectives: This research aims to determine the mineral content of Sapat siam fish specifically Fe, Ca and Zn and the influence of that minerals on appetite regulation in silico.Methods: Analysis of mineral content in Sapat siam fish meat using the AAS method and analysis of the influence of Fe, Ca and Zn minerals using the in-silico method.Results: Sapat siam fish meat contains Fe, Ca and Zn with concentrations of 34.5 ± 0.8485, 1,670 ± 183.8478 and 22.8 ± 0.1414, respectively. The presence of Fe, Ca and Zn in Sapat siam fish meat prediction can binding with ligand Ghrelin, leptin, NPY (Neuropeptide Y), ARC, IL-1β, AgRP Conclusion: Sapat siam fish prediction can stimulate appetite